A genome‐wide association study of early‐maturation traits in upland cotton based on the CottonSNP80K array. Issue 10 (30th July 2018) - Li, Chengqi; Wang, Yuanyuan; Ai, Nijiang; Li, Yue; Song, Jiafeng
Abstract: Genome‐wide association studies (GWASs) efficiently identify genetic loci controlling traits at a relatively high resolution. In this study, variations in major early‐maturation traits, including seedling period (SP), bud period (BP), flower and boll period (FBP), and growth period (GP), of 169 upland cotton accessions were investigated, and a GWAS of early maturation was performed based on a CottonSNP80K array. A total of 49, 650 high‐quality single‐nucleotide polymorphisms (SNPs) were screened, and 29 significant SNPs located on chromosomes A6, A7, A8, D1, D2, and D9, were repeatedly identified as associated with early‐maturation traits, in at least two environments or two algorithms. Of these 29 significant SNPs, 1, 12, 11, and 5 were related to SP, BP, FBP, and GP, respectively. Six peak SNPs, TM47967, TM13732, TM20937, TM28428, TM50283, and TM72552, exhibited phenotypic contributions of approximately 10%, which could allow them to be used for marker‐assisted selection. One of these, TM72552, as well as four other SNPs, TM72554, TM72555, TM72558, and TM72559, corresponded to the quantitative trait loci previously reported. In total, 274 candidate genes were identified from the genome sequences of upland cotton and were categorized based on their functional annotations. Finally, our studies identified Gh_D01G0340 and Gh_D01G0341 as potential candidate genes for improving cotton early maturity. Abstract : 29 SNPs associated with cotton early‐maturation traits were repeatedly detected in at least two environments or two algorithms by GWAS. Six peak SNPs, TM47967, TM13732, TM20937, TM28428, TM50283, and TM72552, exhibited phenotypic contributions of ∼10%. Two candidate genes, Gh_D01G0340 and Gh_D01G0341, may potentially improve cotton early maturity.